Формирующие возможности генератора импульсов магнитного поля - Петков, А.А. (Електротехніка і електромеханіка, 2015)
В работе определены области соотношения параметров схемы генератора импульсов магнитного поля, в которых
возможно формирование трех характерных форм импульсов. Получены соотношения и предложена методика для
выбора параметров элементов разрядной цепи генератора, при которых формируются униполярные импульсы
с монотонным нарастанием и спадом значений. У роботі визначені області співвідношення параметрів схеми генератора імпульсів магнітного поля, у яких можливе
формування трьох характерних форм імпульсів. Отримано співвідношення й запропонована методика для вибору
параметрів елементів розрядного кола генератора, при яких формуються уніполярні імпульси з монотонним
наростанням і спадом значень. Purpose. Determination of areas ratio of the parameters of
the discharge circuit elements of the generator, which ensure
the formation of magnetic field pulses of different shapes.
Methodology. Numerical simulation using dimensionless
variables that determine the nature of the transition process
in the discharge circuit of the generator, and use the procedure for determining the pulse points of meeting the conditions of extremum and the transition through zero. Results.
Obtained a description of the formation of the three specific
areas of waveforms: oscillatory weakly damped oscillatory
strongly damped and unipolar pulse with a monotonic rise
and fall values. A relation to the choice of parameters of elements of the discharge circuit of the generator, which formed
unipolar pulses with a monotonic rise and fall values. Originality. A completed and extended database that implements
the mapping of the formal description of the pulse shape with
a description of areas ratio parameters for high-voltage pulse
discharge circuit test units, with respect to the pulses of current flowing in the formation of the magnetic field. Practical
value. The relations obtained allow to select the parameters
of the discharge circuit elements of the generator designed to
generate test pulses of magnetic field.